Between Convention and Innovation: The Regional Diversity of Gender-Appropriate Language in Job Advertisements for Technician, Educator, IT and Nursing Professions - Філіпп Штанг; Штефані Шольц; Крістіан Вінклер; Сандра Рейманн (Психолінгвістика, 2025)
Purpose. This study investigates the integration of gender-sensitive language in German job advertisements, focusing on trans* inclusion. It aims to assess the extent to which employers in different sectors and regions adhere to guidelines for inclusive language, as outlined in the Bundesverband Trans* (German Trans* Association, 2020) publication, and evaluates the implications for workplace diversity.